Organizational determinants of mobile population administration service performance in Batam City - Risqina Aurisa; Ervin Nora Susanti; Firdaus Hamta (Journal of Applied Business Administration, 2026)
Mobile population administration services (Jemput Bola) have become a critical instrument for extending civil document coverage in archipelagic regions of Indonesia, yet the organizational factors driving their field-level performance remain insufficiently understood. studies have predominantly examined conventional office-based public services and have not integrated leadership, communication, work structure, team dynamics, and organizational environment within a single analytical framework for mobile service contexts; this study aimed to address that gap by analyzing the partial and simultaneous influence of transformational leadership, interpersonal communication, division of work, teamwork, and organizational climate on mobile service performance. A quantitative explanatory study using a census technique was conducted on 50 field officers of the Department of Population and Civil Registration, Batam City, with data collected through validated 5-point Likert scale questionnaires and analyzed using multiple linear regression with SPSS version 26. All five variables had positive and significant partial effects on service performance; simultaneously, the model was significant (F = 25.284; p < 0.001) with an Adjusted R² of 0.713. Teamwork emerged as the most dominant factor (β = 0.312; p = 0.001), followed by transformational leadership (β = 0.245; p = 0.007), while division of work showed the smallest coefficient (β = 0.185; p = 0.046). In mobile service environments characterized by high interdependence and field uncertainty, relational-collective factors (teamwork, leadership) exert stronger influence than structural-procedural factors (division of work), suggesting that proactive public service improvement strategies should prioritize team cohesion and inspirational leadership development.